The Responsibility of The Sleman Regency Government in Providing Tax Education to MSMEs : (Study of PT. Sekawan Makkah Madinah) - Supono, Supono (The Easta Journal Law and Human Rights, 2025)
This study discusses the role of the Sleman Regency Government in providing tax education to Micro, Small, and Medium Enterprises (MSMEs), with a focus on PT. Sekawan Makkah Madinah. The background of this study is based on the importance of tax literacy for MSMEs in improving administrative compliance and supporting the optimization of local tax revenue. The research method used is normative juridical, with a legislative and conceptual approach combined with field data to strengthen the analysis. The results show that the Sleman Regency Government plays a role through the implementation of socialization, training, assistance, and the use of digital technology to encourage tax awareness and compliance among MSME players. This role has had a positive impact, particularly in increasing business actors' knowledge of taxation procedures and legal obligations that must be fulfilled. However, this study also found various obstacles faced by local governments, including low tax literacy among MSME actors, limited human resources, minimal budgets, low business actor participation, and challenges of digitalization and rapid regulatory changes. These obstacles indicate the need for a more systematic strategy, ranging from increasing the capacity of officials, providing applicable educational materials, strengthening digital infrastructure, to improving coordination between relevant institutions.